Ontogenetic changes in stomatal and biochemical limitations to photosynthesis of two co-occurring Mediterranean oaks differing in leaf life span - Juárez-López, Francisco José; Escudero, Alfonso; Mediavilla, Sonia (Tree Physiology, 2008)
A quantitative analysis was applied to the stomatal and biochemical limitations to light-saturated net photosynthesis under optimal field conditions in mature trees and seedlings of the co-occurring evergreen oak, Quercus ilex L., and the deciduous oak, Q. faginea Lam. Stomatal limitation to photosynthesis, maximal Rubisco activity and electron transport rate were determined from assimilation versus intercellular leaf carbon dioxide concentration response curves of leaves that were subsequently analyzed for nitrogen (N) concentration, mass per unit area, thickness and percent internal air space. In both species, seedlings had a lower leaf mass per unit area, thickness and leaf N concentration than mature trees. The root system of seedlings during their third year after planting was dominated by a taproot. A lower leaf N concentration of seedlings was associated with lower maximal Rubisco activity and electron transport rate and with assimilation rates similar to or lower than those of mature trees, despite the higher stomatal conductances and potential photosynthetic nitrogen-use efficiencies of seedlings. Consequently, stomatal limitation to photosynthesis increased with tree age in both species. In both seedlings and mature trees, a lower assimilation rate in Q. ilex than in Q. faginea was associated with lower stomatal conductance, N allocation to photosynthetic functions, maximal Rubisco activity and electron transport rate, and potential photosynthetic nitrogen-use efficiency but greater leaf thickness and leaf mass per unit area. Tree-age-related changes differed quantitatively between species, and the characteristics of the two species were more similar in seedlings than in mature trees. Despite higher stomatal conductances, seedlings are more N limited than adult trees, which contributes to lower biochemical efficiency.
10.1093/treephys/28.3.367
Keywords: A–ci response curves; biochemical capacity; leaf morphology; leaf N allocation; mature trees; Quercus faginea; Quercus ilex; seedlings; Stomatal conductance